2020
DOI: 10.1111/aogs.13820
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of hyperemesis gravidarum: A national register‐based study in Finland, 2005‐2017

Abstract: IntroductionHyperemesis gravidarum is the most common reason for hospitalization in early pregnancy in pregnancies resulting in delivery. Several associative factors indicate that the etiology is likely to be multifactorial. To assess this, we used a unique procedure to compare hyperemetic pregnancies with non‐hyperemetic pregnancies both in different women and in the same women's different pregnancies.Material and methodsData about all pregnancies resulting in delivery in Finland in 2005‐2017 were retrieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 29 publications
4
39
1
2
Order By: Relevance
“…Hyperemesis Gravidarum (HG) is a more severe condition at the extreme end of the pregnancy sickness spectrum. It is estimated to affect 1.5% of pregnant women in the United Kingdom (UK) [2], with rates of 0.8-3.3% reported in other populations [3][4][5][6]. There is no agreed definition of HG, which makes diagnosis, management and research challenging; but HG is typically reported as involving persistent and intractable nausea and vomiting with the triad of more than 5% pre-pregnancy weight loss, dehydration and electrolyte imbalance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperemesis Gravidarum (HG) is a more severe condition at the extreme end of the pregnancy sickness spectrum. It is estimated to affect 1.5% of pregnant women in the United Kingdom (UK) [2], with rates of 0.8-3.3% reported in other populations [3][4][5][6]. There is no agreed definition of HG, which makes diagnosis, management and research challenging; but HG is typically reported as involving persistent and intractable nausea and vomiting with the triad of more than 5% pre-pregnancy weight loss, dehydration and electrolyte imbalance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 90% of pregnant women experience nausea in the early period. It has been reported that nausea during pregnancy is caused by an increase in the level of human chorionic gonadotropin hormone (HCG) [1][2][3]. Hyperemesis gravidarum is a clinical manifestation characterized by increased severity and duration of nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional disorders, dehydration, electrolyte disorders, weight loss, and ketonuria can also be added to the picture, which may worsen the clinical course of the pregnant woman. Hyperemesis gravidarum, which can develop in almost 2% of pregnant women, may be at a level that may require hospitalization in some patients [1][2][3][4][5]. A wide variety of factors play a role in the development of hyperemesis gravidarum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations